Biting Pattern and Seasonality of Filariasis Vector of Mansonia spp. in Endemic Area of Banyuasin Regency, South Sumatera, Indonesia - Pratiwi, Rini; Huda, Adri; Ghiffari, Ahmad; Anwar, Chairil (Open Access Macedonian Journal of Medical Sciences, 2021)
The diversity and biting activity of Mansonia is important to be determined as to predict the incriminated vector and pattern the mosquito behaviour in establishing the vector control programme. The present study has been successfully conducted to investigate the prolonged biting behaviour of Mansonia spp. in two villages in Banyuasin Regency, South Sumatera Province-Indonesia, using Human Landing Collection method (HLC) in indoor and outdoor for 14 months. The result shows that there are 4956 Mansonia spp. mosquitoes collected during the study comprising 6 species: Mansonia uniformis (40.37%), Mansonia annulifera (32.04%), Mansonia indiana (19.97%), Mansonia bonneae (5.28), Mansonia dives (2.14%); and Mansonia annulata (0.18%). The further investigation confirms that Mansonia uniformis (41.254%) and Mansonia bonneae (45.490%) become the most dominant species caught in Sedang village and Muara Sugih village, respectively and find higher biting activities in outdoor than indoor with biting peaked time at approximately 18.00-19.00. However, the biting activities is also observed in daytime, indicating the behaviour change of Mansonia spp. as the nocturnal mosquitoes. Furthermore, the periods of the highest biting rates are found in April 2017 and May 2017 in Sedang village and May 2018 in Muara Sugih Village. The high period of biting activities and behaviours become the valuable information to arrange the further controlling action of filariasis transmission in Sedang and Muara Sugih Villages as the endemic area of filariasis in South Sumatera, Indonesia.